Viewpoint: irrigation water management in a space age - Hafeez, Mohsin; Awan, Usman Khalid (Wiley, 2022)
Climate change and rapid population growth are already putting increasing demand and pressure on the world's freshwater resources. Irrigated agriculture is responsible for about 70% of global freshwater withdrawals, consuming the most amount of water. However, the diverted water in irrigation systems is often not utilized efficiently because of poor water management at different spatial scales, resulting in a system efficiency of only 30–50% in most Asian countries. Typically, improving water management in irrigated areas requires accurate information on various water balance parameters while also considering a changing climate across different spatial scales. There have been technical limitations in getting accurate and reliable information on various key water balance parameters with the conventional approaches used in the recent past. In the twenty-first century, considerable advances have been made in using satellite imagery, including processing and geospatial algorithms, to estimate hydro-meteorological fluxes and relevant components at different spatial scales. This paper provides a perspective on the application of innovative and non-conventional approaches to water resources management in the Murray Darling basin, Australia, the Indus basin, Pakistan and the Amu Darya basin, Uzbekistan. Examples of the state-of-the-art tools described in this paper include: (i) using geoinformatics to monitor the diagnostic and operational performance of large irrigation schemes; (ii) quantifying groundwater and surface water to better manage these two resources using geoinformatics; (iii) forecasting irrigation supply and demand at high spatial and temporal scales using hydrological modelling based on the nodal network; (iv) forecasting crop yield production by satellite remote sensing. The approaches in this study clearly demonstrate that new monitoring and planning tools and methods are highly effective in improving irrigation water management in the ‘space age’ (for the purposes of this paper, space age refers to a period in which earth observation satellites are available to accurately monitor agricultural practices and water balance parameters such as soil moisture and evapotranspiration). The application of these innovative tools can assist in strategizing, diagnosing, monitoring and improving the performance of irrigation systems to grow more crop per drop of water while minimizing environmental impacts and dealing with climate change impacts.